Comrades of the Saddle; Or, The Young Rough Riders of the Plains - Webster, Frank V. (Salt Lake City, UT : Project Gutenberg, 2004)
"Comrades of the Saddle; Or, The Young Rough Riders of the Plains" by Frank V. Webster is a novel crafted in the early 20th century, showcasing the adventurous spirit of youth. The story follows brothers Tom and Larry Alden as they journey from their home in Ohio to spend a summer on a ranch in New Mexico, eager to embrace the life of cowboys and confront challenges along the way. The book promises thrilling escapades, camaraderie, and the discovery of resilience as they encounter situations from escaping a wolf to learning the ropes of ranch life and hunting. The opening of the novel sets an engaging tone, introducing the Alden brothers as they face an unexpected danger$1 (Ba wolf on the prowl$1 (Bwhile racing home from a ball game. Their frantic escape culminates in a heroic rescue by their father and a hired man, highlighting their youthful bravery and strong family bonds. Following this thrilling encounter, the boys learn from their father that they will be heading to Scotland due to an inheritance, but instead, they quickly make arrangements to visit their friends on the ranch. The stage is set for an exciting summer filled with new experiences, as the brothers are determined to embrace the cowboy lifestyle while navigating friendship, adventure, and the perils of life on the plains. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by Al Haines
Keywords: Ranch life -- Juvenile fiction; Cowboys -- Juvenile fiction